2019
DOI: 10.4081/mrm.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of patients with severe acute respiratory infections (SARI): results from the Egyptian surveillance study 2010–2014

Abstract: Background: Respiratory viral and atypical bacterial infections data in Egyptian patients are sparse. This study describes the clinical features and outcomes of patients with severe acute respiratory infections (SARI) in hospitalized patients in Egypt. Methods: SARI surveillance was implemented at Cairo University Hospital (CUH) during the period 2010–2014. All hospitalized patients meeting the WHO case definition for SARI were enrolled. Nasopharyngeal/oropharyngeal (NP/ OP) swabs were collected and samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…In a large Egyptian surveillance study that addressed the epidemiological patterns of severe ARI due to viruses and atypical bacteria in both children and adult population conducted over a 4 year-period Hatem et al reported that no coronavirus was detected among their studied group [47].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a large Egyptian surveillance study that addressed the epidemiological patterns of severe ARI due to viruses and atypical bacteria in both children and adult population conducted over a 4 year-period Hatem et al reported that no coronavirus was detected among their studied group [47].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in Egypt showed that prevalence of Adenovirus infection ranged from 4.5% to 16.7% [19,20,37,47]. Kajon et al [46] investigated 165 respiratory Adenovirus in Argentina, Chile and Uruguay, they reported that the highest prevalence 48.3% was in the age group 0-5 months followed by the age group 6-11 months 34.2% while the least prevalence was in the age group 2-5 years 4.7% with a higher exposure of males 67.5.2% than females 32.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Egypt indicated that viruses were the main causes of SARI in children < 16 years in the pre-pandemic phase with RSV and Adenovirus the being most common viruses and Influenza less common 29 , 30 . The same pattern was found in this study where influenza came third cause of SARI during the late phase of the pandemic.…”
Section: Discussionmentioning
confidence: 99%